The Genocide of the People of Bangladesh - Poghosyan, Narek (YSU Journal of International Affairs, 2021)
The article presents the preconditions for the genocide in Bangladesh, when the state of Pakistan was established in British Muslim-majority British India, which was formedfrom two parts: West Pakistan and East Pakistan. The central government of Pakistan was taking various measures to weaken the identity of the Bengali-speaking population of East Pakistan and to take control of the economy. The way was paved for tensions between the two wings of Pakistan in 1970. The Bangladeshi Awami League won a landslide victory, got a chance to form a government and declared the independence of Bangladesh.It was due to that that Pakistan in 1971 On March 25, he launched military operations in Bangladesh. Pakistan set itself the task of subjugating and colonizing Bangladesh,which it had to achieve through violence, mass killings, the killing of the Bengali elite, intellectuals, the fighters for independence, mass rapes and intimidation. Duringthe nine months of the war for Bangladesh's independence, the Pakistani military and Jamaat-e-Islami militants killed about 3 million people and raped about 250․000 Bangladeshi women and girls. At least 10 million people emigrated to India, 30 million people were forced to leave their homes. However, the genocide campaign carried out by Pakistan did not achieve its goal, moreover, it led to the self-determination and recognition of Bangladesh as an independent state.
Keywords: Pakistan; Genocide of the people of Bangladesh; India; Awami League; operation Searchlight; mass murders; war criminals